2001
DOI: 10.1016/s0092-8674(01)00571-2
|View full text |Cite
|
Sign up to set email alerts
|

LDL Receptor-Related Protein 5 (LRP5) Affects Bone Accrual and Eye Development

Abstract: In humans, low peak bone mass is a significant risk factor for osteoporosis. We report that LRP5, encoding the low-density lipoprotein receptor-related protein 5, affects bone mass accrual during growth. Mutations in LRP5 cause the autosomal recessive disorder osteoporosis-pseudoglioma syndrome (OPPG). We find that OPPG carriers have reduced bone mass when compared to age- and gender-matched controls. We demonstrate LRP5 expression by osteoblasts in situ and show that LRP5 can transduce Wnt signaling in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
1,526
4
24

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,050 publications
(1,591 citation statements)
references
References 47 publications
37
1,526
4
24
Order By: Relevance
“…During development, canonical ligand Wnt3a maintains apical ectodermal cells of limb buds in a highly proliferative state and is, thus, essential to embryonic skeletal development 110, 111. Loss‐of‐function mutations of Wnt coreceptor LRP5 cause reduced bone mass, skeletal fragility, and osteoporosis 112. LRP5 −/− mice have increased tibial fractures because of an overall decrease in bone mass and reduced osteoblast proliferation and function with no effect on bone resorption, whereas single‐allele knockouts of LRP5 lead to an intermediate phenotype of bone mass.…”
Section: Implication Of Canonical Wnt Signaling In Vcmentioning
confidence: 99%
“…During development, canonical ligand Wnt3a maintains apical ectodermal cells of limb buds in a highly proliferative state and is, thus, essential to embryonic skeletal development 110, 111. Loss‐of‐function mutations of Wnt coreceptor LRP5 cause reduced bone mass, skeletal fragility, and osteoporosis 112. LRP5 −/− mice have increased tibial fractures because of an overall decrease in bone mass and reduced osteoblast proliferation and function with no effect on bone resorption, whereas single‐allele knockouts of LRP5 lead to an intermediate phenotype of bone mass.…”
Section: Implication Of Canonical Wnt Signaling In Vcmentioning
confidence: 99%
“…Because sequence variations in COL1A1 , COL1A2 , LRP5 , OPG , and ESR1 increase the risk of low bone mass or osteoporotic fractures, we first examined their possible role in the pathogenesis of stress fractures by scanning all their exons and exon boundaries in the 72 subjects and the 120 controls for mutations using CSGE [14,15,17,20]. The analysis revealed no putative disease-causing mutations.…”
Section: Resultsmentioning
confidence: 99%
“…The function of LRP5 in bone development, however, is indisputable [41]; mutations in LRP5 cause various bone disorders [20,42] and polymorphisms are associated with BMD and bone mineral content in general [43], but also with reduced BMD and fractures [44]. Mouse studies demonstrated that mutations in Lrp5 affect bone formation sensitivity in response to normal mechanical loading [45,46], and thus the LRP5 haplotype A-G-G-C might affect bone sensitivity and response to mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations